Socio-Cultural Learning Based On Digital Technology For Urban Communities Through The Selayar Language Online Dictionary - Ahmadin, Ahmadin (Innovative: Journal Of Social Science Research, 2023)
The development of science and technology as a result of the progress of modern human civilization, among other things, also influences the world of education, especially in learning in various educational units. The use of modern technology with its various advantages then replaces traditional ways of teaching and learning. This paper examines the importance of using digital technology in the form of websites in supporting learning activities, especially in the social and cultural fields, through online dictionaries. The results of this research show that the learning method using website media, namely online dictionaries, has proven to be effective in increasing interest in learning historical and cultural content, especially for university students. Apart from its simple content and online media form, this online dictionary's contents are easier to understand.